Korea: Advance Strategies - Marina Boykova; Mikhail Salazkin (Foresight and STI Governance, 2007)
The economic rise of some Asian countries, which took place in the second half of the twentieth century, drastically changed their culture, and transformed the basic values. In addition to the growth of national wealth, these countries, more importantly, gained a valuable intangible asset - the mentality that assumes a constant generation forestalling strategies - an inexhaustible source of new competitive advantages. Modern Korea - a prime example. The yesterday "Asian miracle" is the future hub for Asian business activity.